The impact and efficiency of medical screening exams in forward treatment areas at New York City public hospitals during the initial COVID‐19 surge. Issue 6 (22nd November 2021) - Moskovitz, Joshua B.; Tan, Timothy; Dilip, Monisha; Khambhati, Kaushal; Smith, Colleen; Sapadin, Joshua; Dauer, Morgan; Chin, Robert; Hammock, Regina; Leno, Richard; Kessler, Stuart; Wei, Eric; et al.
Abstract: Background: New York City (NYC) emergency departments (EDs) experienced a surge of patients because of coronavirus disease 2019 (COVID‐19) in March 2020. NYC Health and Hospitals established rapid medical screening exams (MSE) and each hospital designated areas to perform their MSE. Five of the 11 hospitals created a forward treatment area (FTA) external to the ED to disposition patients before entering who presented with COVID‐like symptoms. Three hospitals used paper‐based, and 2 used an electronic medical record (EMR)‐based MSE. This study evaluated the effectiveness of safely discharging patients home from the FTA while also evaluating the efficiency of using paper‐based versus EMR‐based MSEs. Methods: Charts were reviewed using standardized data extraction templates. Patients discharged from the FTA were contacted by phone, and a structured interview captured additional data regarding subsequent clinical courses. Chi‐square tests were used to compare proportions of patients hospitalized, as well as proportions of patients with vital signs recorded. Mortality rates were compared with Fisher exact test. A logistic regression model with fixed effects to account for clustering at hospitals was used to compare the odds of being sent to the ED for further evaluation based on vital signs and adjusted for age and sex Results: Across 5 EDs, 3335 patients were evaluated in their FTAs from March 17, 2020, to April 27, 2020. A total of 970 (29.1%) patients were referred for further evaluation into the ED, of which 203 (20.9%) were hospitalized and 19 (2.0%) died. Of 2302 patients discharged from the FTA, 182 (7.9%) returned to the ED within 7 days, resulting in 42 (1.8%) hospitalizations and 7 (0.3%) deaths. Facilities using EMR‐MSE discharged more patients from their FTA (81.9% vs 65.3%, P < 0.001) and had similar 7‐day return (9.3% vs 7.1%, P = 0.055) and mortality rates (0.49% vs 0.20%, P = 0.251). Conclusion: MSEs in an FTA are an effective process to disposition patients safely in a high‐volume situation. Differences exist in paper‐ versus EMR‐based approaches, suggesting EMR‐MSEs provide better data, efficiency, and effectiveness. This suggests prioritizing an EMR‐based MSE should be considered in future circumstances.